Lift off!: ruimtecriminologie in Nederland - Eski, Yarin (Onrust is van alle tijden, 2024)
As humanity looks to the stars, space brings both hope for a better future and practical benefits like satellite technology. However, space is also a potential new frontier for crime. Despite official data suggesting no space crime exists, scenarios like astronaut misconduct or space debris as environmental crime are conceivable. The exponential growth of space tourism and missions necessitates criminological attention. Although space law is underdeveloped, criminology has the opportunity to anticipate space crime through tools like extended reality and analog astronaut missions. This proactive approach can foster empirical insights, guiding legal frameworks for addressing future crimes in space.